Luteolin: exploring its therapeutic potential and molecular mechanisms in pulmonary diseases - Lv, Jialian; Song, Xinyue; Luo, Zixin; Huang, Duoqin; Xiao, Li; Zou, Kang (Frontiers in Pharmacology, 2025)
Luteolin is a flavonoid widely found in plants, including vegetables, botanical drugs, and fruits. Owing to its diverse pharmacological activities, such as anticancer, oxidative stress protection, anti-inflammatory, and neuron-preserving effects, luteolin has attracted attention in research and medicine. Luteolin exhibits therapeutic effects on various pulmonary disease models through multiple molecular mechanisms; these include inhibition of activation of the PI3K/Akt-mediated Nuclear Factor kappa-B (NF-κB) and MAPK signaling pathways, as well as the promotion of regulatory T cell (Treg) function and enhancement of alveolar epithelial sodium channel (ENaC) activity (alleviating inflammation and oxidative stress responses). Luteolin has therapeutic effects on chronic obstructive pulmonary disease (COPD), acute lung injury/acute respiratory distress syndrome (ALI/ARDS), pulmonary fibrosis, allergic asthma, and lung cancer. Luteolin, a naturally occurring polyphenol, is poorly water-soluble. The oral route may be ineffective because the gut poorly absorbs this type of flavonoid. Therefore, although luteolin exhibits significant biological activity, its clinical application is limited by challenges associated with its poor water solubility and low bioavailability, which are critical factors for its efficacy and pharmacological application. These challenges can be addressed by modifying the chemical structure and enhancing pharmaceutical formulations. We summarized the research advancements in improving the solubility and bioavailability of luteolin, as well as the effects of luteolin on various pulmonary diseases and their related mechanisms, with the aim of providing new ideas for researchers.